IMPLEMETASI PROGRAM PENINGKATAN DIVERSIVIKASI DAN KETAHANAN PANGAN (STUDI KEGIATAN KAWASAN RUMAH PANGAN LESTARI DI KELURAHAN AGROWISATA KOTA PEKANBARU) - Susi Anggreni; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Implementation here actions taken after public policy is determined, to achievethe goals or objectives to be achieved. Implication of the Program to IncreaseDiversification and Food Security (Study of Sustainable Food House Area Activities inthe Agro Tourism Village of Pekanbaru City) there are several problems found byresearchers including the Budget target for this activity is not appropriate if done in thecity of Pekanbaru because it is not Stunting District Sustainable Food Houses LikeIncreasing Awareness and Public Participation in realizing Food Consumption has notyet been carried out, Processing the results of farms that have not been implemented,and Demonstration Plots which are still difficult to control by group members. Thepurpose of this study is to find out how the implementation of KRPL and the inhibitingfactors of KRPL activities at KWT Sentosa Wisata. The theoretical concept used byDaniel Mazmanian and Paul Sabatier in Nugroho (2014: 666) which consists ofIndependent Variables, Interventing Variables and Variables outside the Policy. Theresearch method is a type of qualitative research case study approach, the selection ofinformants using Purposive Sampling techniques. Data collection techniques throughobservation, interviews, and documentation. Research Results Implemation ofPrograms to Increase Diversification and Food Security (Study of Sustainable FoodHouse Area Activities in Agrowisata Village, Pekanbaru City) shows that the KRPLactivity is not yet maximal. The inhibiting factors include Individual and GroupInterests, and Member Participation. It is better if Pekanbaru Food SecurityDepartment can motivate activities to run optimally, and groups maintain cohesivenesswithin the group, participate in KRPL activities in order to be able to add insight inconducting KRPL.Keywords: Policy, Implementation, Sustainable Food House Area